Dental arch width in overweight and normal-weight subjects - Cynthia Yzquierdo-Correa; Weyder Portocarrero-Reyes; Marcos J. Carruitero; Paola Claudet-Angulo (Universidad de Concepción., 2019)
Objective: To compare the width of the dental arches between overweight and non-overweight subjects . Materials and Methods: A cross-sectional comparative study was carried out with 54 subjects from 8 to 13 years of age, 27 normal-weight and 27 overweight. The presence of overweight was assessed according to the Quetelet index. To determine the width of the dental arches, measurements of the upper and lower intercanine and intermolar width were obtained with a digital calibrated Vernier caliper. The comparison between the dental arch width of normal-weight and overweight subjects was performed using the Mann-Whitney U test. Results: Statistically significant differences were found in the intercanine and intermolar widths between overweight and non-overweight subjects (p<0.05). Conclusion: The dental arches were wider in overweight subjects compared to those of normal-weight.